Georgia : Financial Sector Assessment Program-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
There have been significant improvements in both the quality of regulation and the supervisory approach since the 2007 FSAP. Many amendments to existing laws, new laws, and regulations have been introduced, aimed at addressing shortfalls identified in the 2007 FSAP. These improvements will be evident throughout this assessment. At the same time, a number of weaknesses have been identified. Among these is an operational risk within the NBG's own Banking Supervisory Department. There has been a very high level of staff turnover in recent years due to a lack of salary competitiveness vis-a-vis the commercial banks, and there appears to be over-reliance on key personnel. Also, the level and type of staff training need to be expanded. While the NBG puts significant effort into understanding the risk profile of each individual bank and the banking system as a whole, more attention is needed to improve the quality of risk management of the banks. In a number of areas, notably bank licensing, the NBG relies on its broad supervisory powers to carry out its functions in the absence of detailed explicit powers. While this regime generally seems to work well in practice, it could leave the NBG open to challenge where these broad powers are not supported by more granular powers. Recently, several amendments to the legislation have been introduced in order to address these shortcomings.